Blood transfusion trends by disease category in the United States, 2000 to 2014 - Roberts, Nicholas (Transfus Apher Sci, 2020)
BACKGROUND: Better understanding of blood usage rates could identify trends in transfusion practices over time and inform more efficient management. METHODS: Inpatient admissions from the Healthcare Cost and Utilization Project National Inpatient Sample and State Inpatient Databases were analyzed for packed red blood cell (PRBC), plasma, platelet, and whole blood (WB) transfusions. The transfusion rates per admission and per prevalent case were calculated. Prevalence estimates were from the Global Burden of Disease 2017 study (GBD). RESULTS: From 2000 to 2014, blood usage rates for most causes peaked around 2010. Across all causes, PRBC were the most commonly transfused component, followed by plasma, platelets, and WB. However, the relative use of each type varied by cause. Nutritional deficiencies (1.75 blood product units across all components per admission; 95% uncertainty interval (UI) 1.62 – 1.87), neoplasms (0.95; 0.87 – 1.04), and injuries (0.92; 0.86 – 0.98) had the greatest blood use per admission. Cardiovascular diseases (96.9 units per 1,000 prevalent cases; 89.3 to 105.0) and neoplasms (92.7 units per 1,000 prevalent cases; 84.3 to 101.5) had the greatest blood use per prevalent case. Across all admissions, over three million blood units were saved in 2014 compared to 2011 due to transfusing at a reduced rate. CONCLUSIONS: Blood transfusions rates over the last years have decreased in the United States. This decline occurred in most disease categories, which points towards broad strategies like patient blood management systems being effective with potentially additional disease specific improvements like changes in surgical techniques.